The Effect of Load Variations on The Performance Efficiency of Gas Turbines at PLTG UPDK Tello Makassar - Kasmiranti, Nur; Syahrul, Syahrul; Massikki, Massikki; Iswal Burhan, Muhammad (Energy Insights, 2025)
The demand for the changing electricity system so that power plants also experience load changes. As is known, PLTG Tello Makassar is the last priority to operate under certain conditions. Therefore, the purpose of this study is to prove the occurrence of load changes and find out the causes of efficiency that experience data changes in each load operated on the turbine. In this study, a type of quantitative descriptive research was used using the Brayton cycle calculation method on the formula of gas turbine efficiency equations. After conducting research, data was obtained that the Tello Makassar GE Unit 2 PLTG operates with loads that vary from 8 MW to 28 MW. The average turbine efficiency of each load variation is 8 MW with an average turbine efficiency of 54.34%, 10 MW with an average turbine efficiency of 38.87%, 15 MW with an average turbine efficiency of 56.13%, 16 MW with an average turbine efficiency of 41.78%, 17 MW with an average turbine efficiency of 65.61%, 18 MW with an average turbine efficiency of 25.73%, 20 MW with an average turbine efficiency of 51.86%, and 28 MW with an average turbine efficiency of 56.75%. The difference in average efficiency is affected by fluctuations in electricity demand that fluctuate every hour. The efficiency of gas turbines also varies even at the same load due to different environmental and operational temperature factors and pressures at any time. From the results of the study, overall turbine efficiency data was obtained where the lowest efficiency of 13.95% was at a load of 15 MW at 17.00 WITA, while the highest turbine efficiency of 88.27% was at a load of 8 MW at 14.00 WITA.